Efficient multicomponent synthesis of diverse antibacterial embelin-privileged structure conjugates - Martín Acosta, Pedro (2020)
A library of embelin derivatives has been synthesized through a multicomponent reaction from embelin (1), aldehydes and privileged structures such as 4-hydroxycoumarin, 4-hydroxy-2H-pyran-2-one and 2-naphthol, in the presence of InCl3 as catalyst. This multicomponent reaction implies Knoevenagel condensation, Michael addition, intramolecular cyclization and dehydration. Many of the synthesized compounds were active and selective against Gram-positive bacteria, including one important multiresistant Staphylococcus aureus clinical isolate. It was found how the conjugation of diverse privileged substructure with embelin led to adducts having enhanced antibacterial activities.